Study on mechanical properties and microstructure of steel-polypropylene fiber coal gangue concrete - Li, Jiuyang; Chen, Li; Luo, Jingwei; Zhu, Yuepeng; Fan, Xinmei; Hu, Guangchao (Frontiers in Materials, 2023)
Incorporating coal gangue into the concrete matrix can realize the utilization of solid waste and reduce the use of natural aggregate. To improve the mechanical properties of coal gangue concrete, this paper designs four-level and four-factor orthogonal tests with coal gangue ceramide substitution rate, coal gangue ceramide sand substitution rate, steel fiber content, and polypropylene fiber content as independent variables. Through multidimensional data analysis of the test results, The main and secondary factors of compressive strength of hybrid fiber coal gangue concrete from strong to weak are the replacement rate of coal gangue ceramic sand, the replacement rate of coal gangue ceramic grain, the content of steel fiber and the content of polypropylene fiber. The optimal content is 30% coal gangue ceramic particle, 25 30% coal gangue ceramic sand, 0.75 1% steel fiber, and 0.2% polypropylene fiber. The grey prediction model GM (1,5) is obtained, which can predict the concrete strength well within the range selected in this paper. The influence of fiber and coal gangue on the microstructure was studied by scanning electron microscopy, and the influence law of interfacial transition zone on the strength of concrete was explored, which provided a theoretical basis for the study of solid waste utilization of coal gangue.